Sana dati - Tarog, Jerrold; Poe, Lovi; Avelino, Paulo; Trinidad, TJ; Metric Films (Firm). ([Place of production not identified] Metric Films, 2013)
"Andrea Gonzaga is about to marry a man she doesn't love when a mysterious guest arrives and suddenly reminds her of the man she truly loves."
Summary taken from: https://www.imdb.com/title/tt3031048/?ref_=fn_al_tt_1
Produced by Daphne Chiu, Jerrold Tarog; music by Jerrold Tarog; cinematography by Mackie Galvez.
Lovi Poe, Paulo Avelino, TJ Trinidad.
DVD
In Tagalog
Keywords: Drama; Romance